Pamphlet architecture 11-20. - Holl, Steven, (Pamphlet architecture, 2011)
Hybrid Buildings / Joseph Fenton -- Building Machines / Robert McCarter, editor -- Edge of a City / Steven Holl -- Mosquitoes / Ken Kaplan and Ted Krueger -- War and Architecture / Lebbeus Woods -- Architecture as a Translation of Music / Elizabeth Martin -- Small Buildings / Mike Cadwell -- Reading Drawing Building / Michael Silver -- Seven Partly Underground Rooms and Buildings / Mary-Ann Ray